Preungual drug delivery systems of Terbinafine Hydrochloride Nail Lacquer - Jan, Sabreen; Bora, Divyakumar; Bhise, Kiran (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of the present investigation was to formulate and evaluate the terbinafine hydrochloride nail lacquer as preungual drug delivery system for the treatment of onychomycosis.Terbinafine hydrochloride was chosen as the model drug, and the formulations were prepared with and without polymer Eudargit RL 100 (Eu) within the concentration range of 1% to 5% (w/v) in the polymeric system. Then, these lacquers were compared for glossiness, film formation, drying rate, smoothness of flow, and nonvolatile content,The in vitro studies were preformed on the artificial membrane and bovine hooves in solvent A (phosphate buffer, pH 7.4; and methanol, AR grade, in the ratio of 4:1). The result obtained indicated that the nail lacquer formulation F2 (1.3% of the drug and 1.3% of Eudargit RL100) showed good release of the drug. Thus nail lacquers can be used as a successful tool for targeted drug delivery for onychomycosis.